Proyecto de factibilidad para la implementación de una empresa productora y comercializadora de escobas de fibra de palma africana en el cantón Tena, provincia de Napo, para el año 2016 - Paredes Arellano, Froilan Bladimir (2017)
Ecuador is wonderful and has a diversity of natural resources an optimal climate fused with the fertile land, becoming a productive country The Ab broom is a product that is used for cleaning in homes, offices, warehouses, becoming more accepted by Ecuadorian families, Being this product one of the main economic support to the families of the city of Tena allowing this work to become a solution for the socio-economic development of the same. As a general objective we have to determine the feasibility for the implementation of an African palm fiber broom marketer in Tena, Napo province. As specific objectives we have to determine through the market study the supply and demand of the product, conduct a technical study to determine the installed capacity, the location of the company and engineering of the project and the technical and technological requirements to be used in the new company, To propose an administrative structure and the legal formation of the company, to carry out the financial study to determine the amount of economic resources that are necessary for the project, to carry out a financial evaluation through the financial indicators such as the NPV, TIR, RB / C, PRC and AS. That is why it is vitally important to approach the present project since the broom sector is in a critical situation since they do not have a productive process planning working in inappropriate conditions with a lack of training and technification for the elaboration of this product causing a high cost of the same, limiting the sources of income of those who carry out this activity In the present work of investigation was used methods and techniques by means of which the acquired information could be analyzed and thus to realize a determined study of the whole project, using the technique of the survey that was applied to the families of the city of Tena with a sample of 377 surveys, and 5 interviews to the suppliers such as supermarkets and grocery stores where they offer African palm fiber brooms, resulting in an effective demand of 70,700 fiber brooms; And the present offer amounts to 9,600 brooms; As a result there is an unsatisfied demand for 61,100 brooms of African palm fiber for year zero In the technical study it was established that according to the machinery to be acquired the company will have an installed capacity of 52,000 brooms of African palm fiber. The company will be located in the province of Napo, canton Tena, parish Tena in the neighborhood Vista Hermosa street Manuel Maria Rosales and Pullurco. The engineering of the project was done as is the description of the productive process, equipment and materials of production to be used until the finished product was obtained and finally the design and distribution of each one of the areas of the fiber broom processing plant was developed. The organizational study was carried out in which it was established that the company will have five hierarchical levels: legislative, executive, advisor, support, and operational. The organizational structure indicates the important aspects of the structure of the company, therefore, it was elaborated three organizational charts that are the structural one, positional and functional, such as the manual of functions that contains the set of norms and tasks that will develop each of the officers that conform the company, in addition requires hiring 6 people, creating equal number of sources of work. The company will be incorporated under the legal form of Limited Liability Company; its corporate name is Producer Company of African Fiber Palm Brooms - Comercializadora Arellano la Barredora Cía. Ltda. Its term will be 10 years. In the financial study it was determined that the project had an investment Of $ 130.680,58 and will be financed with a shareholder contribution of 71,69% of the total investment corresponding to $ 93.680,50 and the 28,31% corresponding to a remaining $ 37,000.00 will be obtained from a loan in the Bantuador A rate of 11,26% annual interest for 10 years. The financial evaluation indicators show positive and encouraging results to ensure a good return on the project where the Net Present Value (NPV) was calculated $ 15.659,68 Internal Rate of Return (TIR) 13,93%, Cost Benefit Ratio (RBC) shows that for every dollar invested in the production of fiber brooms the company earns USD $ 0.30 cents, the Capital Recovery Period (PRC), recovers in 5 years 5 months and 15 days, and in the sensitivity analysis the project supports an increase in costs of up to 6,82% and a decrease in revenues up to A 5,24%. It is concluded that the investment is profitable for the company, because the percentage of profit that has been considered from 30 % during the 10 years of project life and according to the results obtained it was determined that the project is feasible placing the product in the market at $ 2.80 the competitive advantage that will differentiate the MARKETER ARELLANO LA BARREDORA CÍA. LTDA. It will be the quality and price of the product. It is recommended to develop new designs and types of brooms such as brooms in medium size for easier use of adolescents since many homes are the ones who do the cleaning, so we would take full advantage of the machinery that the company has and thus have a variety of products that customers can choose. Finally the bibliography and annexes were presented.